Enhancing gate turn-off thyristor blocking characteristics by low temperature defect passivation technology. (30th June 2021) - Wu, Pei-Yu; Chen, Min-Chen; Chang, Ting-Chang; Zheng, Hao-Xuan; Jin, Fu-Yuan; Tan, Yung-Fang; Tu, Yu-Fa; Tsai, Xin-Ying; Huang, Jen-Wei; Chang, Kuo-Jen; Liu, Guan-Shian; Tsai, Tsung-Ming
Abstract: In the past, gate turn-off (GTO) thyristors were commonly used to either increase the length of the drift region or reduce the doping concentration to increase high-voltage and high-power applications. However, this results in an on-resistance ( R on ) increase. In this study, we applied a supercritical fluid (SCF) treatment to devices which has the advantage of high permeability and low-temperature processing to passivate SiC-GTO bulk defects. After the proposed defect passivation, the breakdown voltage has been improved by 8% without increasing on-state resistance. In addition, the leakage current has also been suppressed more than 30% in average. This study also uses electrical analysis to understand the characteristics of the devices after SCF treatment, and then discusses the passivation mechanism of materials of the devices from this treatment.